Functionalized Zn@ZnO Hexagonal Pyramid Array for Dendrite‐Free and Ultrastable Zinc Metal Anodes - Kim, Ji Young; Liu, Guicheng; Shim, Ga Young; Kim, Hansung; Lee, Joong Kee (Advanced functional materials, 2020)
Here, an electrode comprising a Zn hexagonal pyramid array (HPA) coated with a functionalized ZnO layer (Zn@ZnO HPA) is prepared using a periodic anodizing technique. The HPA structure markedly increases the electroactive surface area of Zn anode, thus decreasing the local current density. Furthermore, the functionalized ZnO coating layer has a gradient thickness that plays an important role in the selective deposition of Zn ions and the mitigation of side reactions at the interface. The electrochemical stability of the Zn@ZnO HPA electrode, which is closely related to the electroactive surface area and charge transfer resistance, is determined by the “split” value, i.e., ratio of current‐off to current‐on time, a parameter of the periodic anodizing process. Compared with the pristine Zn‐based symmetric cell, the Zn@ZnO HPA‐based symmetric cell is safely operated in the investigated experimental range with the 10‐fold improved running life and 25‐fold enhanced current density without Zn dendrite growth. Moreover, the Zn@ZnO HPA/MnO2 battery exhibits outstanding long‐term cyclability (nearly 100%) with greater than 99% Coulombic efficiency after 1000 cycles at a current density of 9 A g−1. This periodic anodizing technique for ultrastable Zn metal anodes is expected to contribute to the development of inherently safe energy storage systems. A Zn hexagonal pyramid array coated with a functionalized ZnO layer (Zn@ZnO HPA) prepared via a periodic anodizing process acts as a Zn metal electrode for inherently safe Zn ion aqueous batteries. The unique Zn@ZnO HPA anode shows improved stability without dendrite formation owing to the large surface area and guided Zn ion plating.